Only mostly devastated - Gonzales, S., 1992- (Wednesday Books, 2020)
When his aunt's illness keeps Ollie in North Carolina, he hopes his summer fling with Will can grow into something more, but at school Will proves to be a completely different--and firmly closeted--man.